Comprehensive analysis of systemic, metabolic, and molecular changes following prospective change to low-carbohydrate diet in adults with type 2 diabetes mellitus in India - Bhandarkar, Nikhil Suresh; Shetty, K. Bhujang; Shetty, Naren; Shetty, Keerthy; Kiran, Anupama; Pindipapanahalli, Narendra; Shetty, Rohit; Ghosh, Arkasubhra (Frontiers in Nutrition, 2024)
Purpose: South Asians, especially Indians, face higher diabetes-related risks despite lower BMI compared to Whites. Limited research connects low carbohydrate/ketogenic diets (LCHF) to metabolic changes in this group. Systematic studies are needed to assess the diet's long-term effects, including ocular health.In this prospective, observational study, 465 candidates, aged 25-75 years with type 2 diabetes included with institutional ethics approval. Total 119 subjects were included in the final study assessment based on the availability of pathophysiological reports, tears and blood samples collected at baseline, 3 rd , and 6 th months. Serum and tear samples were analysed by an enzyme-linked lectinsorbent assay to examine secreted soluble protein biomarkers such as IL-1β (Interleukin 1 Beta), IL-6 (Interleukin 6), IL-10 (Interleukin 10), IL-17A (Interleukin 17A), MMP-9 (Matrix Metalloproteinase 9), ICAM-1 (Intercellular Adhesion Molecule 1), VEGF-A (Vascular Endothelial Growth Factor A), and TNF-A (Tumour Necrosis Factor Alpha). A Wilcoxon test was performed for paired samples. Spearman's correlation applied to test the strength and direction of association between tear biomarkers and HbA1c. p < 0.05 was considered significant.Results: After a 3-and 6-month LCHF intervention, fasting blood sugar decreased by 10% (Δ: -14mg/dL; p<0.0001) and 7% (Δ: -8mg/dL; p<0.0001), respectively. Glycated hemoglobin A1c levels dropped by 13% (Δ: -1%; p<0.0001) and 9% (Δ: -0.6%; p<0.0001). Triglycerides reduced by 22% (Δ: -27mg/dL; p<0.0001) and 14% (Δ: -19mg/dL; p<0.0001). Total cholesterol fell by 5.4% (Δ: -10.5mg/dL; p<0.003) and 4% (Δ: -7mg/dL; p<0.03), while low-density lipoprotein decreased by 10% (Δ: -11.5mg/dL; p<0.003) and 9% (Δ: -11mg/dL; p<0.002). High-density lipoprotein increased by 11% (Δ: 5 mg/dL; p < 0.0001) and 17% (Δ: 8 mg/dL; p<0.0001). At the first follow-up, tear proteins ICAM-1, IL-17A, and TNF-α decreased by 30% (Δ: -2739pg/mL; p<0.01), 22% (Δ: -4.5pg/mL; p<0.02), and 34% (Δ: -0.9pg/mL; p<0.002), respectively. At the second follow-up, IL-1β and TNF-α reduced by 41% (Δ: -2.4pg/mL; p<0.05) and 34% (Δ: -0.67pg/mL; p<0.02). Spearman's correlation between HbA1c and tear analytes was not statistically significant.The LCHF diet reduces hyperglycemia and dyslipidemia. Changes in tear fluid protein profiles were observed, but identifying promising candidate biomarkers requires validation in a larger cohort.